Role of Karanjadi Ghrita for the Management of Bhagandara (Fistula-in-Ano) (AYUSHDHARA, 2022)
In Ayurveda, fistula-in-ano is known as Bhagandara which considered in Asta Mahagada. This disease has been considered in Asta Mahagada in Ayurvedic classics due to its complications and more recurrence rate. Nowadays this disease is increasing due to more prone to sedentary life style. Using of Kshara Sutra therapy in case of Bhagandara is for a long time. Kshar Sutra therapy is big revolution in the case of this disease, but it has still challenges for finding satisfactory cure. It has some complications like severe post-procedural pain, burning sensation, inflammation, discharge, itching and enhances the Pitta Dosha. To overcome these complications of Kshara Sutra, a clinical study was conducted that using of Karanjadi Ghrita by their local application after the therapy of Kshara Sutra. Mainly, the contents of Karanjadi Ghrita have cleaning and healing properties. Maximum ingredients of this medicine were having Tikta and Kashaya in Rasa. Tikta and Kashaya rasa promote the ulcer healing by his Shodhana and Ropana properties. Some of the drugs of Karanjadi Ghrita have analgesic properties, reduce inflammation qualities and reduces burning sensation properties. Karanjadi Ghrita has stopped bacterial growth and their toxicity by the reduce infection and reduce toxicity properties of ingredients. It proves that Karanjadi Ghrita reduces the Pitta Dosha and overcome the complications. It was found that Karanjadi Ghrita with Kshara Sutra was more efficient and can be considered a better method.